Moving through spaces - leisure walking and its psychosocial benefits for well-being: a narrative review - Marta Zurawik (Termedia Publishing House, 2020)
Leisure walking provides an escape from routines and daily lives, and offers positive experiences, such as fascination with nature, reflection, and mental relaxation. The processes of exploring and observing nature while walking build bonds between people and spaces. In walking, people explore personal capabilities and overcome challenges associated with demanding landscapes, which enhances feelings of satisfaction and achievement. Furthermore, sharing spaces and similar positive experiences with others while walking promote social interactions and a sense of belonging that combats feelings of loneliness and benefits well-being. Ample research on physical activity, including walking, has explored the role of psychological, social, and environmental factors in the activity participation, and recognised its benefits for mental health and well-being. This paper reviews literature in the field of leisure and environmental psychology to present the evidence of the positive relationships between leisure walking in the natural environment and its psychological and social benefits for well-being.